Screen Reader on the Wall: Tell Me, How Do I Look on the Photo? - Hafiar, Hanny; Nurzaman, Mohamad; Puspitasari, Lilis; Dewi, Retasari; ., Yustikasari; Wirman, Welly (International Journal of Engineering and Technology, 2018)
Screen reader has become one of the tools that can accommodate the needs of blind people. A lot of information can be accessed directly by blind people independently and do not have to depend on other people's help. Along with the development of technology, there is also the need for the visually impaired, especially for young people with visual impairments who are familiar with information communication technology, to be able to enjoy an image or photo through their smartphone screen. This need arises along with their interaction with the environment that provides knowledge about images that can be enjoyed on a photo, or personal experience before they experience blindness. In addition, there are still some things that are expected by blind people to screen reader capabilities as the main tool they use to "see". Therefore, this study conducted a study on mapping the needs of blind people to the screen reader function through aspects of accessibility tools, based on information sharing patterns, which foster new needs within the people with visual impairments.Â